2021
DOI: 10.7759/cureus.14759
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Alpha-1 Antitrypsin Deficiency Causing Pulmonary Emboli and Pulmonary Bullae

Abstract: Alpha-1 antitrypsin deficiency is an autosomal co-dominant disease known for different genetic alterations in the serine protease inhibitor enzyme by which different disease phenotypes can manifest. The lung and the liver are the most common organs involved. The severity of the disease depends on the phenotypes involved. However, emerging evidence shows that this disease can impact multiple organ systems and may even develop regardless of the phenotype. We describe a case of a young man with a known history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The results of the large cohort study carried out in 15 586 COVID-19 patients at a Cleveland clinic have shown that 9.2% of COVID patients suffered from COPD [ 186 , 190 ]. This fact is in agreement with the data of other authors showing that COPD patients without any other comorbidities run the higher risk of severe COVID-19 [ 187 ]. At the same time, the increased expression of ACE2 receptor in case of SARS-CoV-2 infection was not associated with the phenotype of the disease [ 191 , 192 ].…”
Section: α 1 -Proteinase Inhibitor Under Normal ...supporting
confidence: 93%
See 2 more Smart Citations
“…The results of the large cohort study carried out in 15 586 COVID-19 patients at a Cleveland clinic have shown that 9.2% of COVID patients suffered from COPD [ 186 , 190 ]. This fact is in agreement with the data of other authors showing that COPD patients without any other comorbidities run the higher risk of severe COVID-19 [ 187 ]. At the same time, the increased expression of ACE2 receptor in case of SARS-CoV-2 infection was not associated with the phenotype of the disease [ 191 , 192 ].…”
Section: α 1 -Proteinase Inhibitor Under Normal ...supporting
confidence: 93%
“…Protection against respiratory infections [4,19,50,146,160,193,209] "Acute phase" protein Increased content of α 1 -PI; is considered as a universal response to a pathological process. Increased levels of this protein have been detected in case of COVID-19 [17, 18, 160-162, 164, 202] Oxidative stress marker Increase in α 1 -PI correlates with the oxidative stress development [168][169][170][171] NET inhibition Inhibition of elastase involved in NET formation, the development of thrombosis [50,187,[203][204][205] α 1 -PI dysfunction Genetic and acquired deficiency of the inhibitor: the damage to the active center during oxidation, the effects of ecologically unfavorable environmental factors, smoking. Degradation by proteinases with the formation of proinflammatory peptides [171-174, 183, 184] Therapeutic effect of α 1 -PI Inhibition of membrane and plasma proteinases.…”
Section: Anti-apoptotic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a meta-analysis of 17 studies on PI*MS heterozygotes has shown that, despite reduced plasma AAT levels, these subjects are not at risk of airway obstruction, COPD or greater FEV 1 decline [10]. However, a case report revealed an association between this genotype and the presence of lung bullae [11]. In asthmatic patients, heterozygosity for AAT with PI*MZ and PI*MS genotypes is associated with small airway dysfunction and with lung air trapping [12].…”
Section: Introductionmentioning
confidence: 94%